Respostas
respondido por:
1
P.A (3, 1 , -1 , 3....)
Primeiro termo (a1) = 3
Razão (r) = 1-3 = -2
Pela fórmula geral:
aN= a1 + (N-1).r
a60= 3 + (60-1).(-2)
a60= -118+3
a60= -115
Primeiro termo (a1) = 3
Razão (r) = 1-3 = -2
Pela fórmula geral:
aN= a1 + (N-1).r
a60= 3 + (60-1).(-2)
a60= -118+3
a60= -115
DanJR:
Obs.: r = a_{n} - a_{n - 1}. Ou seja, a razão é dada pela diferença entre um termo qualquer e seu antecessor.
respondido por:
0
r = a2 - a1
r = 1 - 3
r = - 2
an = a1 + (n - 1).r
a60 = a1 + (60 - 1).r
a60 = a1 + 59r
a60 = 3 + 59.(-2)
a60 = 3 - 118
a60 = - 115
r = 1 - 3
r = - 2
an = a1 + (n - 1).r
a60 = a1 + (60 - 1).r
a60 = a1 + 59r
a60 = 3 + 59.(-2)
a60 = 3 - 118
a60 = - 115
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás